Informatics Consideration on the Hierarchical System of Rare Diseases Clinical Care in China - GONG Mengchun; GUO Yanying; ZHENG Xihong; FAN Junkang; LIU Peng; NIU Ling; YANG Yining; ZOU Xiaoguang (罕见病研究)
The diagnosis and treatment resources for rare diseases in China are highly imbalanced. The basic diagnosis and treatment capabilities are weak, the diagnosis period for patients is long, and the rates of missed diagnosis and misdiagnosis are relatively high. The establishment of a hierarchical diagnosis and treatment system is the inevitable approach to enhancing the diagnosis and treatment standards of rare diseases. Currently, the implementation of the domestic hierarchical diagnosis and treatment system for rare diseases still confronts numerous challenges, such as ambiguous referral standards and processes of primary medical institutions, and ineffective information interaction among institutions at all levels. Thus, it is essential to facilitate high-level information construction for the hierarchical diagnosis and treatment of rare diseases. This paper explores the process of constructing a multidisciplinary joint remote diagnosis and treatment platform and a health management platform through informatization, with the hope of establishing two closed loops of digital diagnosis and treatment services and health follow-up management for patients with rare diseases, as well as achieving timely diagnosis and lifelong health management for patients. It integrates and optimizes auxiliary diagnostic tools, promotes the rapid dissemination of rare disease diagnosis and treatment experiences to the grassroots, enhances the information construction level of the hierarchical diagnosis and treatment system, and endeavors to address the practical predicament of weak diagnosis and treatment capabilities of rare diseases in grassroots medical institutions. Additionally, this paper proposes an essential approach for multi-dimensional independent innovation to guide the popularization of efficient and high-quality rare disease diagnosis and treatment services. By encompassing innovating the rare disease diagnosis and treatment collaboration network and multidisciplinary diagnosis and treatment model, facilitating the application of the latest biomedical and informatics technologies to the grassroots, and constructing a national intelligent data platform for rare disease innovation, a new model for rare disease services with Chinese characteristics will be established. This will significantly enhance the medical treatment level of rare diseases in China and strive for more benefits for patients.